The Application of Albert Bandura's Social Cognitive Theory in Education and Parenting - Ulil Abshar; Annisak Rofifah (Advances In Education Journal, 2026)
This study examines the application of Albert Bandura’s Social Cognitive Theory within educational and parenting contexts by addressing the problem of how personal factors, behavior, and environment interact to shape students’ learning outcomes. The research aims to explain the mechanisms of observational learning, self-efficacy, and reciprocal determinism in influencing students’ academic performance and developmental competencies. Data were collected through literature review, analysis of empirical studies, and examination of documented cases related to classroom practices and parenting strategies. The findings indicate that modeling, reinforcement, and environmental structuring significantly enhance students’ cognitive strategies, motivation, and self-efficacy. The study also shows that effective educational environments and supportive parenting strengthen students’ adaptive behaviors and learning autonomy. These results highlight the importance of integrating positive models and self-efficacy building approaches into instructional and parenting practices. In conclusion, Social Cognitive Theory offers a robust framework for improving educational processes and promoting holistic student development.